Gender and the Body Size Aftereffect: Implications for Neural Processing - Brooks, Kevin R.; Baldry, Evelyn; Mond, Jonathan; Stevenson, Richard J.; Mitchison, Deborah; Stephen, Ian D. (Frontiers in Neuroscience, 2019)
Prolonged exposure to wide (thin) bodies causes a perceptual aftereffect such that subsequently-viewed bodies appear thinner (wider) than they actually are. This phenomenon is known as visual adaptation. We used the adaptation paradigm to examine the gender selectivity of the neural mechanisms encoding body size and shape. Observers adjusted female and male test bodies to appear normal-sized both before and after adaptation to bodies digitally altered to appear heavier or lighter. In Experiment 1, observers adapted simultaneously to bodies of each gender distorted in opposite directions, e.g. thin females and wide males. The direction of resultant aftereffects was contingent on the gender of the test stimulus, such that in this example female test bodies appeared wider while male test bodies appeared thinner. This indicates at least some separation of the neural mechanisms processing body size and shape for the two genders. In Experiment 2, adaptation involved either wide females, thin females, wide males or thin males. Aftereffects were present in all conditions, but were stronger when test and adaptation genders were congruent, suggesting some overlap in the tuning of gender-selective neural mechanisms. Given that visual adaptation has been implicated in real-world examples of body size and shape misperception (e.g. in anorexia nervosa or obesity), these results may have implications for the development of body image therapies based on the adaptation model.